MODEL PENINGKATAN DAYA TARIK WISATA MELALUI PENGEMBANGAN KUALITAS PELAYANAN PADA WANA - Salahuddin, Salahuddin; Haifa, Haifa; Jatmiko, Hadi (Relasi : Jurnal Ekonomi, 2015)
<!–[if gte mso 9]> <![endif]–> Jemberhasseveral attractionsincludeCape Wana PapumaWatuUloBeach, Rembanganarea, beacharea ofNusaBarongandsomeagro-owned PT. Nusantaraplantationandsomehaveprivateestates. Management ofthese attractionsneed tobeoptimized. Tourism developmentis donetomakethemore interestingsightsandexcel. The purpose ofthe study: 1). FormulateStandard OperatingProcedure(SOP) travelservicesinCapePapumaWanaJember, 2). Testedagainststandard operatingprocedurespreparedand3). Analyzing thetraveler’s satisfaction with the serviceatthe CapeecotourismPapumaJemberbeforeand after implementation ofthe SOP.Analysisandimprovement ofquality of careusing theprinciplesFocussGroup Discussions (FGD). To findthe differencebetweentouristsatisfactionbeforeand after implementation ofSOPdistributedquestionnairesto touristswhothenanalyzed byt-testanalysis showedno significant differencebetween thesatisfaction ofCapeecotourismtravelersPapumabeforeimplementationand after implementation ofStandard Operating Procedure(SOP). The analysis showedthatafterthe application ofSOP, ecotourismtourist satisfactionisthehighestPapumaCapeDimensionalTangible/Intangible(X1), thenthedimension ofEmpathy(X5), while thelowestsatisfactionratingisthedimensionRealibilty/Reliability(X2) andAssurance/warranty(X4). Thusthe managersWanaCapePapumais to maintainandenhance thetangibledimension/Tangible(X1) and theEmpathyDimension(X5) andincreaseDimensionsReliability(X2) andAssurance(X4), by regularlyconduct trainingtoimprove thequality of services tothe resourceshumansbothto employeesandpartners. <!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–>MODEL PENINGKATAN DAYA TARIK WISATA MELALUI PENGEMBANGAN KUALITAS PELAYANAN PADA WANA <!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>